Long-Term Functional Outcomes and Multidisciplinary Management after Ileorectal Duhamel Pull-Through for Total Colonic Aganglionosis—20-Year Experience in a Tertiary Surgical Center - Bhandarkar, Kailas; De Coppi, Paolo; Cross, Kate; Blackburn, Simon; Curry, Joe (European Journal of Pediatric Surgery, 2023)
Introduction Management of patients with total colonic aganglionosis (TCA) is challenging for pediatric surgeons. The purpose of this study was to review our institution's 20-year experience regarding long-term outcomes and multidisciplinary team management of these patients after an ileorectal Duhamel pull-through procedure.Materials and Methods Retrospective review was conducted for all patients diagnosed with TCA in our tertiary institution. Data were collected on demographics, clinical presentation, complications, need for additional surgery, and long-term effects on bowel function.Results Of a total of 202 patients with Hirschsprung's disease, 13 were diagnosed with TCA (6.4%). Clinical presentation was variable. Eleven presented in neonatal period with distal bowel obstruction and two presented with constipation in early infancy. Ileorectal Duhamel pull-through was performed in all patients. Median follow-up was 13 years. Eleven are toilet trained, of whom five are fully continent. Six continue to have problems with bowel continence or constipation. One developed recurrent episode of Hirschsprung's associated enterocolitis. Two patients had stoma re-established. Patients experiencing difficulties in bowel function are jointly managed by a multidisciplinary team consisting of surgeons, gastroenterologists, pediatric psychologists, and clinical nurse specialists.Conclusion TCA can be associated with significant long-term morbidity. Nearly half of the patients in this series have ongoing problems with bowel continence requiring a permanent stoma in some. Diligent follow-up coupled with inputs of a multidisciplinary team has greatly helped manage these complex patients in our institution.
Keywords: total colonic aganglionosis; Hirschsprung's disease; Hirschsprung's associated enterocolitis; ileorectal Duhamel pull-through